APLIKASI MONITORING PASANG BARU INDIHOME DAN KINERJA SALES PADA PT. TELKOM AKSES - Anwar, Rezky Izzatul Yazidah (Pusat Riset dan Inovasi Nasional, 2022)
PT. Telkom Access is a subsidiary of PT. Telekomunikasi Indonesia, Tbk (Telkom) whose shares are wholly owned by Telkom. Telkom Access is engaged in the business of providing construction services and managing network infrastructure. PT. Telkom Access still uses facilities in the form of Google Drive to help monitor the results of new installations of Indihome and there has been no sales performance for its employees to use, but this is not completely smooth, sometimes it is slow and cannot be accessed due to several things such as the internet network is experiencing interference, poor access. concurrently, and other constraints, so as to access and monitor the final results of the design to make